The design of cake slicer for bakery industry / Amirrul Aiman Muhammad - Muhammad, Amirrul Aiman (2022)
The idea of cake slicer is due to the struggle that modem cake industry had gone through. Thus, this cake slicer project is an invention to reduce the man-works that wasting a lot of time especially in bakery industry during cutting their cake. This cake slicer will help reduce time spent by bakers to cut each slice. The objective of this product is to design and fabricate a cake slicer that will slice the cake with the exact same dimension at one time. Other than obtaining the same dimension, the baker also will not have to cut the cake slowly because using this product by only using one motion the cake can be sliced into 8 pieces. The very first step is to design the suitable cake slicer and then fabricate it so it will be benefits to the bakery industry. At the end of the project, a cake slicer with functioning design will be able to help the bakery industry. For future research, the cake slicer can be improve by adding an automatic mechanism to it. Hence, no more manpower is required anymore to slice cake.